Wage and employment effects of the Olympic Games in Atlanta 1996 reconsidered - Arne Feddersen; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2009)
We estimate the economic effects of the 1996 Atlanta Olympic Games. Our difference in difference model checks for serial correlation and allows for a simultaneous test of level and trend effects, but otherwise follows HOTCHKISS, MOORE, & ZOBAY (2003) in this journal. We were not able to reconfirm their finding that the Games had significant positive employment effects. We do, however, reaffirm their result of no significant wage effects.
Keywords: H54; R12; L83; 330; Olympic Games; sports economics; mega events